2017
DOI: 10.1634/theoncologist.2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tertiary Lymphoid Structure Associations and Their Prognostic Relevance in HER2 Positive and Negative Breast Cancers

Abstract: Despite recent interest on the clinical value of tumor infiltrating lymphocyte (TIL), little was known on the clinical significance on their spatial organization as tertiary lymphoid structures (TLS). Although TLS showed similar relationships with clinicopathologic features and biomarkers as TIL, the prognostic value of TLS, particularly in HER2 positive cancers, was independent of TIL. Moreover, tumor infiltration could be present in TLS which appears to be related to tumor invasion in HER2 negative cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 31 publications
1
93
1
Order By: Relevance
“…A staging method used conjointly with the Breslow thickness to describe the depth of melanoma tumour invasion into the skin. lymphatic invasion, increased pathological nodal stage and nodal involvement in the HER2 − (particularly oestrogen receptor-positive) tumours 92 . One could speculate that tumour cells that penetrate TLSs may metastasize more readily to regional lymph nodes.…”
Section: Clark Level Of Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…A staging method used conjointly with the Breslow thickness to describe the depth of melanoma tumour invasion into the skin. lymphatic invasion, increased pathological nodal stage and nodal involvement in the HER2 − (particularly oestrogen receptor-positive) tumours 92 . One could speculate that tumour cells that penetrate TLSs may metastasize more readily to regional lymph nodes.…”
Section: Clark Level Of Invasionmentioning
confidence: 99%
“…A pilot study (28 patients) indicated that TLSs were more common in high-grade muscle-invasive bladder cancer than in the non-muscle-invasive cancers 91 . In breast cancer, high-grade tumours were found to be twice more prone to exhibit TLSs than low-grade tumours, and the most aggressive tumour grade, grade 3, is an independent predictor for TLS formation in patients with human epidermal growth factor receptor 2 (HER2; also known as ERBB2) − tumours 66,92,93 . Nevertheless, the link between the presence of TLS and tumour grade and the decrease in prognostic value of TLSs during tumour progression do not occur in all cancers, with TLSs being found to retain their prognostic value with high prognostic impact in advanced NSCLC 22 , pancreatic cancer 63 and colorectal cancer 62 in large cohorts (TABLe 2).…”
Section: Tlss During Tumour Progression the Link Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] In addition, the presence of sites promoting cell-cell interactions, such as tertiary lymphoid structures (TLSs), have shown to hold predictive power of treatment outcome in HER2-positive tumors. [11][12][13] Evidently, the characterization of the cell type population within tumors and their environment is imperative to understand the disease.…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, TLS has been associated with lymphatic invasion, increased pathological nodal stages and nodal involvement in some tumors. 34 TLS has even been detected in metastases in parallel with primary tumors. 35 In addition, the presence of TLS with desmoplastic melanomas have a higher response rate to PD-1 blockade.…”
Section: Discussionmentioning
confidence: 99%